(untitled) (Research, Society and Development, 2022)
To evaluate available evidence in the literature of iron deficiency anemia in pregnant women with low adherence to ferrous sulfate. This is an integrative literature review, being consulted in the following databases: LILACS, PUBMED, SCIELO, BVS, MEDLINE. During the period from September to October 2021. Through the descriptors: “Pregnancy AND iron deficiency anemia”, “ferrous sulfate AND iron deficiency anemia”, “pregnancy AND iron deficiency anemia”. A total of 5,892 articles were obtained, after reading the title, abstract and full text of the articles, a total of 10 articles remained at the end. Among the factors responsible for the low adherence to ferrous sulfate by pregnant women, side effects, age, race, low education, multiparity, number of consultations, family income and inadequate prenatal care stand out. In this way, it was observed how important is the qualified assistance of the health professional in the prenatal consultation and the use of strategies for better adherence to the supplement.